Targeted Price Controls on Supermarket Products - Aparicio, Diego; Cavallo, Alberto (The Review of Economics and Statistics, 2021)
We study the impact of targeted price controls on supermarket products in Argentina. Using daily prices for controlled and noncontrolled goods, we examine the effects on inflation, product availability, entry and exit, and price dispersion. First, price controls have only a small and temporary effect on inflation that reverses soon after the controls are lifted. Second, contrary to common belief, controlled goods are consistently available for sale. Third, firms respond by introducing new varieties at higher prices. Overall, our results show that targeted price controls are just as ineffective as more traditional policies of price controls in reducing aggregate inflation.